2018
DOI: 10.6000/1929-5634.2018.07.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vernonia amygdalina Leaf on Nutritional and Biochemical Parameters in Alloxan-Induced Diabetic Rats

Abstract: The effects of Vernonia amygdalina leaf on the nutritional and biochemical parameters in alloxan-induced diabetic rat were investigated. Vernonia amygdalina (VA) leaf was squeeze-washed, dried, pulverized and mixed with standard feed at 2.5%, 5%, 10% and 20%. The proximate nutrient composition of the standard and prepared rations was determined. The Vernonia amygdalina incorporated rations and standard ration were fed to alloxan-induced diabetic rats for 70 consecutive days. Thereafter the nutritional and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The diets were formulated as described by Amaechi et al [10]. Briefly, standard diet containing 83% corn starch, 10% casein, 2% vegetable oil, 3% rice bran and 2% vitamin and mineral mix was prepared.…”
Section: Formulation Of Experimental Dietmentioning
confidence: 99%
“…The diets were formulated as described by Amaechi et al [10]. Briefly, standard diet containing 83% corn starch, 10% casein, 2% vegetable oil, 3% rice bran and 2% vitamin and mineral mix was prepared.…”
Section: Formulation Of Experimental Dietmentioning
confidence: 99%
“…Research has shown that bitter leaf is an embodiment of valuable compounds such as saponins, flavonoids, alkaloids, and tannins etc [3]. Extract of V. amygdalina subjected to hydrodistillation revealed the presence of linoleic acid and oleic acid which are both essential [4] as well as α-pinene and eucalyptus linalool [5].…”
Section: Introductionmentioning
confidence: 99%